PENATALAKSANAAN FISIOTERAPI PADA KONDISI LOW BACK PAIN et CAUSA SPONDYLOSIS LUMBAL DENGAN MODALITAS ULTRASOUND, TRANSCUTANEUS ELECTRICAL NERVE STIMULATION DAN WILLIAM’S FLEXION EXERCISE DI RSUD KRATON PEKALONGAN - Indah Ayu Fibriani; Eko Budi Prasetyo (Universitas Widya Husada Semarang, 2018)
Low Back Pain et causa Spondylosis Lumbar is a degenerative process that occurs in the corpus and the intervertebral disc due to a decrease in the density ofthe corpus intervertebra and narrowing of the corpus intervertebral causedthinning of the disc, along with lower back pain due to stress back muscles,tendons, ligaments with symptoms such as Local pain not accompanied bytingling, weakness or neurological disorders. Problems of physiotherapy includepain silent press and motion in the lower back spasm, decreased trunk musclestrength, range of motion limitations trunk, decreased functional activity. In thiscase the selected intervention technologies to overcome the above problems byusing ultrasound modality, transcutaneus electrical nerve stimulation andWilliam's flexi exercise. Design research with descriptive method used in thepreparation of scientific papers is a case study. The taking of scientific papers isdone in RSUD Kraton Pekalongan. Based therapy that has been done obtained the following results: (1)decrease in silent pain becomes T6 T1 = 8 = 2, the tenderness T1 = 2 to T6 = 1,and the motion pain becomes T1 = 4.8 T6 = 1, (2) a decrease in muscle spasm atT1 = spasm, at T6 = spasm but decreases, (3) an increase in muscle strength m.Flexor trunk T1 = 2 to T6 = 3, at m. extensor trunk T1 = 2 to T6 = 3, (4) anincrease in the scope of flexion trunk T1 = 4 to T6 = 6, the extension trunk T1 = 4to T6 = 6, lateral dextra trunk T1 = 3 to T6 = 8, lateral sinistra Trunk T1 = 8 to T6= 9 (5) an increase in functional activity T1 = 18% to T6 = 2%. With the results obtained it can be concluded that the use of the modalitiesof physiotherapy with ultrasound, transcutaneus electrical nerve stimulation andWilliam's flexi physiotherapy exercise can help the problems arising from lowback pain lumbar spondylosis et causa.